Pearls and Pitfalls in Cosmetic Oculoplastic Surgery - Hartstein, MD, FACS, Morris E.; Massry, MD, FACS, Guy G.; Holds, MD, FACS, John B. (Springer New York : Imprint: Springer, 2015)
Pearls and Pitfalls in Cosmetic Oculoplastic Surgery, Second Edition addresses the need among surgeons for cleanly distilled and clinically relevant information. The second edition of this popular text highlights the changes and updates to the ever expanding field of facial cosmetic surgery. There are updates regarding the advances, for example in blepharoplasty techniques, fillers and filler techniques, periorbital fat grafting, brow lifting techniques, and midface rejuvenation. Additionally, nearly every chapter has full color illustrations to bring each one to life. This concise and practical "how to" book is written and edited by experts in their fields and offers "here's how I do it" advice on the most commonly performed procedures. Each chapter becomes the voice of an expert and experienced colleague, reminding readers of the pearls and pitfalls of each procedure. These pearls will lead to more efficient techniques, fewer complications, and enhance outcomes for physicians and their patients.